(untitled) (Research, Society and Development, 2023)
The objective of this paper is to elucidate the possible influences of memory fallibility on testimony, by applying the scientific methodology of literature review. Memory is an essential aspect of human cognition, which enables the individual to encode, store and retrieve information about past events, formed by a complex process, multiple stages and brain regions. It plays a crucial role in testimonial evidence, which refers to a fact reported by a person who actually witnessed it or has knowledge of some relevant fact, but this does not mean that it will always be accurate, since it can be influenced by a variety of internal and external factors. The influences can be as diverse as attention, emotions, motivations, age, illness, injury, even the media, conversations with others, and the conduct of the hearing. The legal operator must take these aspects into consideration when performing his work, seeking to reduce the influences and mitigate the power of this type of evidence, in addition to giving priority to material evidence instead of relying exclusively on testimonial evidence, thus enabling greater assertiveness.